Pengaruh Modal Sosial Terhadap Keberdayaan Ekonomi Petani Padi Sawah Desa Labulu-Bulu Kecamatan Parigi Kabupaten Muna - Wa Ode Suriyati; Hartina Batoa; Awaluddin Hamzah (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
This study aimed to determine the effect of social capital on the economic empowerment of lowland rice farmers in Labulu-Bulu Village, Parigi District, Muna Regency. Determination of the location was carried out deliberately in that this village is one of the villages that applies social capital in cultivating lowland rice in Parigi District. The population in this study were 350 farmers and the sample was taken at the 10% level so that the sample of this study was 35 respondents, and was carried out in October 2020 until it was finished. Data analysis used multiple linear regression with the help of SPSS 20. The results showed that there was a simultaneous influence of social capital, namely trust, network, social norms and participation on the economic empowerment of lowland rice farmers in Labulu-Bulu Village, Parigi District, Muna Regency. Based on the results of the simultaneous calculation of the effect of trust, network, social norms and participation on the economic empowerment of farmers, at the 5% significance level, the Fcount value is 8,058 with the Ftable value of 2.49.